Application of crack tip plasticity based fatigue model on high temperature alloy HAYNES® 282®. (January 2015) - Ismonov, Shakhrukh; Loghin, Adrian; Hanlon, Timothy; Shen, Chen
Highlights: Plasticity based fatigue model is employed to predict fatigue crack growth rates. Model is calibrated for HAYNES® 282® alloy at 1200F and 1400F. FCGR predictions are presented along with the test data. Model captures average cyclic crack growth rate behaviors for 0.05 <  R  < 0.5. Predictions do not capture accelerated fatigue crack growth rates at lower loads. Abstract: Confined crack tip plasticity model is employed to predict time independent fatigue crack growth rate (FCGR) behavior of HAYNES® 282® alloy at temperatures 1200F and 1400F. Crack growth tests were done in lab air, vacuum and steam environments at load ratios R = Kmin /Kmax ranging from 0.05 to 0.5. Calibrated model predicts average cyclic crack growth rate behavior of the material reasonably well. Predictions do not capture the accelerated fatigue crack growth rates observed in the data at low load levels. Such effects are believed to be caused by environmentally driven factors, which are not expected to be predicted by plasticity based models.